Suffrage extension, social identity, and redistribution: the case of the Second Reform Act. (6th April 2018) - Seghezza, Elena; Morelli, Pierluigi
Abstract: The most widely accepted interpretation of the Second Reform Act is the redistributivist hypothesis . This interpretation, however, is at odds with the absence of redistributive measures in the years after the 1867 Reform Act. Drawing on the social identity hypothesis, we argue that the British elite was convinced that skilled workers were not demanding the right to vote in order to obtain redistributive measures, and therefore they had no misgivings about granting this right to this group of workers. To confirm this, we use an event study to show that the various parliamentary stages of the Second Reform Act had no effect on Consol yield.